ÉTUDES ETHNOBOTANIQUE ET ETHNOLINGUISTIQUE DES RESSOURCES FORESTIÈRES LIGNEUSES UTILISÉES PAR LA POPULATION DU COULOIR ÉCOLOGIQUE DU PARC NATIONAL DE KAHUZI-BIEGA (R D. CONGO) - Jean De Dieu, Mangambu Mokoso; Jean-Yves, Aluma Kabika; Van Diggelen, Ruurd; Amour de Dieu, Rugenda-Banga Runiga; Félicien, Mushangalusa Kasali; Adolphe, Chibembe Safaria; Honorine, Ntahobavuka Habimana; Birhashirwa, Radar Nishuli; Elmar, Robbrecht (European Scientific Journal, ESJ, 2015)
This article focuses on the use and the vocabulary of 323 specimens representing 52 species woody species that were collected from three ethnosocio-linguistic groups (Shi, Tembo and Pygmies) living in the ecological corridor of Kahuzi -Biega National Park (KBNP). This area consists of a transitional forest between the vegetation of the plains and the mountains. The study has shown that the food and, pharmacological knowledge are almost detained by the pygmies. The analyses carried out show that this population takes interest to the forestry species they consider to be useful though they are found in a protected area. The total ethno botanical value of species is not really significantly to different ethno-socio-linguistic group to another (p-value = 0.514; F = 1.08 and df = 3). The Kruskal-Wallis test shows that the different organs do not have the same importance for the use of the population. (F = 1.08 and df = 3). The correlation between the ethno botanical use value in relation to the number of species use is significant (R² = 0.084%). Specific vocabularies ethnonymical in Mashi and Kitembo express the same common meanings of species on the formal and semantic plans. These three tribes share several ethnonymical concepts, which could be a symbol indication of the subsistence of a pygmy original language, forgotten to the Bantu languages that have borrowed them. Despite the importance of trees in the hall of the Park, we suggest conservative actions or reforestation could protect.